KARAKTERISTIK PENDIDIKAN KARATER SISWA PADA JENJANG PENDIDIKAN DASAR - Ramin Ramin (Tatar Pasundan: Jurnal Diklat Keagamaan, 2018)
Educating children character of the "now" era requires an effort that is not simple.Various negative behaviors and even crime are not the least done by children of elementary age. It makes parents worry about their child's future. Madrasah Ibtidaiyah and SDIT are basic educational institutions that have almost the same characteristics that is dominant in religious education. From the content of the subjects, giving some general knowledge, guiding attitude, and fostering behavior are the hallmarks of both. However, each of these institutions has its disadvantages, whereas madrasahs on knowledge dissemination generally, while SDIT on the socialization of religious education to the wider community. Key words: Educating Character, Basic Education, religious education